(untitled) (Andamios, Revista de Investigación Social, 2014)
Different research programs in philosophy have defined the notions of analyticity and apriority. Contemporary perspectives: Boghossian (2000), Peacocke (2000), Kitcher (1980, 2000), Horwich (2000) —just to mention some cases— face the problem of defining the extension of such concepts. The purpose of this paper is: to offer the reader, in a single useful article, a fine and delimited analysis of the paradigmatic logicist definition of analyticity that cause the contemporary discussions: Frege (1879, 1874) and ii. Carnap (1935, 1947). In this way, the reader will have the conceptual tools to follow properly the classical and contemporary controversy available on this matter, in philosophy of language, philosophy of logic and the epistemology